An Intellectual in the Corridors of Power - Acharya, Jaya Raj (Journal of Foreign Affairs, 2021)
Introduction: A reviewer of my book Yadu Nath Khanal: Jivani ra Vichar (Yadu Nath Khanal: Life and Thoughts) wrote: “Prithvi Narayan Shah unified Nepal, Bhanubhakta Acharya standardised Nepali language and Yadu Nath Khanal intellectualised Nepal’s foreign policy”. Indeed Professor Yadu Nath Khanal made outstanding contributions in explaining Nepal’s foreign policy to the international community in modern terminology. His thoughts on Nepal, Nepali literature and Nepal’s foreign policy are compiled in a book Nepal’s Non-Isolationist Foreign Policy (Kathmandu: Satyal Prakashan, 2000) that has 100 articles divided into five sections. Professor Khanal was a scholar, literary critic and successful practitioner as well as a thinker of Nepal’s foreign policy. But above all, he was an intellectual par excellence. I will begin this biographical sketch of Professor Khanal with his birth and academic career and conclude it with an extract from Professor Kamal P. Malla (1936-2018), himself a great scholar, who described Professor Khanal as “an intellectual in the corridors of power”.